Is There A Relationship Between Parental Communication and HIV/AIDS Knowledge in Students? - Nofita Dewi Kok Mesa; Crystin Evangelin Watunglawar; Dwi Astuti; Angela Librianty Thome; Fenska Narly Makualaina (Indonesian Journal of Global Health Research, 2025)
The high prevalence of sexually transmitted disease infections resulting in high rates of HIV/AIDS is related to very low preventive behavioral practices. Adolescence is very closely related to psychological development in the puberty period and is accompanied by sexual development. HIV/AIDS cases occur most often in adolescents and young adults. Effective communication between parents and adolescents is used as the main strategy in an effort to increase responsible sexual behavior and minimize risky sexual behavior in adolescents. Objectives to find out the relationship between parental communication and HIV knowledge in students in junior high school The research method used was a correlation analytical description research design with a cross sectional approach with 79 research samples. The sampling method is using the Probability Sampling technique by means of Random Sampling. The analysis test used was the Pearson Test with a significance level of p < 0.005. The results of the study were obtained in the Relationship of Parental Communication to HIV/AIDS Knowledge in Students with a significance value of 0.003 (p value < 0.005) with a correlation value (r) of 0.611 which means a positive correlation with a strong correlation power. Parents have a big role in growth and development, in children's behavior facing puberty, and it is important for parents to build communication with children. Communication between parents and adolescents is a form of parenting process that has an important influence on adolescent sexual behavior.